Adat Perkahwinan Melayu Dahulu Dan Sekarang - Mohd Afiq, Mahmud (Universiti Malaysia Sarawak, (UNIMAS), 2016)
This research program is to identify the indigenous tradition of modern and traditional Malay wedding in Kota Samarahan, Sarawak. The research methodology was qualitative methods of observation interviews and documentation. The findings showed that there were differences of traditional and modern. The difference is like a wedding dress material and management during the wedding day.